Occurrence of Leaf Blight on Cosmos Caused by Alternaria cosmosa in Korea - Deng, Jian Xin (Plant Pathol J, 2015)
In 2011, a leaf blight disease was observed on cosmos (Cosmos bipinnatus) leaves in Nonsan, Korea. The causal pathogen was isolated and identified based on morphological and molecular approaches. Morphological characteristics of the pathogen matched well with the Alternaria cosmosa and also easily distinguishable from Alternaria zinniae reported from cosmos seeds by producing branched beak. Phylogenetically, the pathogen could not be distinguished from A. passiflorae based on the sequence analysis of a combined data set of Alt a1 and gpd genes. However, A. passiflorae was distinguished from the present species by having conidiophores with 4 to 5 conidiogenous loci. The results indicate that the present Alternaria species is A. cosmosa. Pathogenicity tests revealed that the isolate was pathogenic to the leaves of Cosmos bipinnatus. This is the first report of Alternaria blight disease caused by A. cosmosa on cosmos in Korea.